Akademiliv (English) - Språkbanken Text (University of Gothenburg, 2025)
Akademiliv is the Sahlgrenska Academy’s staff magazine online.
This corpus contains the English versions of the articles.

Akademiliv är Sahlgrenska akademins personaltidning på nätet.
Denna korpus innehåller de engelska versionerna av artiklarna.
Akademiliv (engelska)
Keywords: Language Technology (Computational Linguistics); magazines; news texts; non-fiction; corpus; Natural Language Processing; Språkbehandling och datorlingvistik